Biomimetic Surface with Tunable Frictional Anisotropy Enabled by Photothermogenesis‐Induced Supporting Layer Rigidity Variation. Issue 2 (16th November 2018) - Ji, Zhongying; Yan, Changyou; Ma, Shuanhong; Zhang, Xiaoqin; Jia, Xin; Wang, Xiaolong; Zhou, Feng
Abstract: Anisotropic friction of widespread biological surfaces with micro‐ and nanostructures oriented to supporting layer is proved to be crucial for the purpose of locomotion or transporting items in nature, which is therefore attracting extensive attention. Herein, variation of supporting layer rigidity induced dynamic control of anisotropic friction of biomimetic surface with structures oriented to supporting substrate is demonstrated. The biomimetic surface with oriented hook‐like spines microstructures embedded in polymeric substrate is fabricated by three‐dimensional (3D) printing followed by transfer reproduction. Incorporation of Fe3 O4 nanoparticles with excellent near‐infrared (NIR)/infrared (IR) photothermogenesis in the substrate results in its variable rigidity with light on/off, which achieves the tunable anisotropic friction performance of the biomimetic surface. A proof‐of‐concept device with the function of Velcro type strip is demonstrated to unsnap the fastener by remote NIR/IR light, revealing its promising for designing intelligent control devices. It is believed that this novel anisotropic friction controllable system with photothermogenesis‐induced supporting layer rigidity variation will provide wide and potential applications in various fields including sensors, robots, and other bionic devices. Abstract : Biomimetic surface with microstructures oriented to substrate is fabricated with three‐dimensional (3D) printing followed by transfer reproduction, where photothermal Fe3 O4 nanoparticles are incorporated into the substrate. With the supporting layer rigidity variation induced by photothermogenesis of Fe3 O4, the resultant surface realizes light triggered tunable frictional anisotropy, which will be promising in sensors, robots, and many other bionic devices.